USING UZBEK NATIONAL PATTERNS IN TECHNOLOGY LESSONS IN PRIMARY SCHOOL (Web of Technology: Multidimensional Research Journal, 2024)
The article discusses the types of patterns used in Uzbek traditional handicraft production. Patterns are an important material in technology lessons in elementary grades, since familiarizing younger students with folk traditions using patterns in various products contributes to the development of general outlook, creative imagination, as well as the education of artistic taste, interest in national culture, respect for their work and the work of their peers.